Analisis problematika kompetensi guru di Indonesia era society 5.0 - Pela, Pela Pratama Putri; Mifta Aulia Rahmi; Ahmad Ridwan; Rully Hidayatullah (STAI AL-AMIN, 2025)
The Society 5.0 era demands adaptive, creative, and competent human resources, including in the field of education. Teachers as the front line in the learning process are required to have competencies that are in accordance with technological developments and the needs of the 21st century. However, in Indonesia, various problems still overshadow teacher competencies, ranging from pedagogical, professional, social, to personality aspects. This article aims to analyze the problems of teacher competencies in Indonesia in facing the challenges of Society 5.0. This study uses a descriptive qualitative approach through literature studies. The results of the analysis show that there is still a gap between the demands of teacher competencies and the reality in the field. Collaborative efforts are needed between the government, professional organizations, and educational institutions to strengthen teacher competencies so that they are able to answer the challenges of the increasingly complex digital era.